Shared mechanisms of neural circuit disruption in tuberous sclerosis across lifespan: Bridging neurodevelopmental and neurodegenerative pathology - Litwa, Karen (Frontiers in Genetics, 2022)
Tuberous Sclerosis (TS) is a rare genetic disorder manifesting with multiple benign tumors impacting the function of vital organs. In TS patients, dominant negative mutations in TSC1 or TSC2 increase mTORC1 activity. Increased mTORC1 activity drives tumor formation, but also severely impacts central nervous system function, resulting in infantile seizures, intractable epilepsy, and TS-associated neuropsychiatric disorders, including autism, attention deficits, intellectual disability, and mood disorders. More recently, TS has also been linked with frontotemporal dementia. In addition to TS, accumulating evidence implicates increased mTORC1 activity in the pathology of other neurodevelopmental and neurodegenerative disorders. Thus, TS provides a unique disease model to address whether developmental neural circuit abnormalities promote age-related neurodegeneration, while also providing insight into the therapeutic potential of mTORC1 inhibitors for both developing and degenerating neural circuits. In the following review, we explore the ability of both mouse and human brain organoid models to capture TS pathology, elucidate disease mechanisms, and shed light on how neurodevelopmental alterations may later contribute to age-related neurodegeneration.